Peralihan Hak Milik atas Tanah berdasarkan Hibah Wasiat dengan Penerima Wasiat Meninggal Dunia di Provinsi Sumatera Barat - Maria Susanti; Azmi Fendri Fendri; Yasniwati Yasniwati (UNES Law Review, 2023)
A person who dies does not stipulate everything regarding his inheritance, so the distribution of the assets left behind will be carried out based on the law (ab intestato). Meanwhile, if someone before he died had written his will in a deed, then his inheritance was divided based on a will (testament). The legal consequences of the will if the beneficiary dies before the transfer of land rights is carried out, namely: a) If the beneficiary dies before the testator or testator dies, the will is declared null and void, b) If the beneficiary dies after the giver of the will dies first world, the will remains valid due to the validity of the gift based on a will, namely after the giver of the will dies.